Strengthening Social Inclusion and Empowerment of Women through the Wahid Foundation Damai Village in Batu City - Zeid bin Smeer; Mubasyiroh Mubasyiroh; Inayatur Rosyidah (Budapest International Research and Critics University, 2022)
The involvement of women in public forums is very limited and still has a domestic role. The paternalistic socio-cultural system plays a role in giving birth to gender inequality in social inclusion in people's lives. In this context, the Wahid Foundation designed an initiative called Desa Damai. This research includes qualitative descriptive research and field research. Data were collected through observation, interviews and focus group discussions in stages. This study uses Miles and Huberman's interactive analysis technique and community entrepreneurship supported by savings and loan cooperatives.